2011
DOI: 10.2169/internalmedicine.50.4340
|View full text |Cite
|
Sign up to set email alerts
|

Acute Transverse Myelitis and Acute Motor Axonal Neuropathy Developed after Vaccinations against Seasonal and 2009 A/H1N1 Influenza

Abstract: Acute transverse myelitis (ATM) has been described as an uncommon complication of vaccinations and is rarely accompanied by inflammatory peripheral neuropathy. We report a case of a 77-year-old woman who developed ATM and acute motor axonal neuropathy (AMAN) following vaccinations against seasonal and 2009 A/H1N1 influenza. She manifested ophthalmoplegia, quadriparesis and sensory impairment. MR imaging showed a longitudinally-extensive spinal cord lesion, and nerve conduction study revealed motor axonal polyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
(10 reference statements)
0
12
1
Order By: Relevance
“…Currently, the disease is also presumed to be caused by effects of the immune response following virus infections rather than by direct viral infections in the spinal cord. In some cases, AM was diagnosed after vaccinations that could lead to abnormal immunological responses (Sato et al, 2011). In this study, 35% of patients had symptoms of pre-existing infections, which is lower than the 40% reported in previous studies.…”
Section: Pre-existing Infectionscontrasting
confidence: 71%
“…Currently, the disease is also presumed to be caused by effects of the immune response following virus infections rather than by direct viral infections in the spinal cord. In some cases, AM was diagnosed after vaccinations that could lead to abnormal immunological responses (Sato et al, 2011). In this study, 35% of patients had symptoms of pre-existing infections, which is lower than the 40% reported in previous studies.…”
Section: Pre-existing Infectionscontrasting
confidence: 71%
“…The fast implementation of the vaccines used against the H1N1 influenza pandemic was unprecedented on a global scale and evoked anticipated concerns of unknown adverse effects. Numerous studies have since raised or dealt with the apprehension that this vaccine could be associated with Guillain-Barré syndrome,31 32 33 34 transverse myelitis,35 36 narcolepsy in children,37 38 39 retrograde amnesia,40 or other adverse events 233 41 42 However, such analyses usually cannot be produced in time to respond to the rapidly evolving safety concern when reports of vaccine related adverse events spread quickly throughout society by the internet and mass media, leading to the loss of public confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GM1 antibodies were positive in that patient, and the partial effectiveness of steroid therapy was described. Sato et al reported a case of acute transverse myelitis and AMAN after H1N1 influenza vaccination, with negative anti-ganglioside antibodies (11). They performed highdose immunoglobulin and steroid treatment, however, the patient did not experience a significant recovery.…”
Section: Discussionmentioning
confidence: 99%